CHOKEPOINTS IN SUSTAINING ORGANIC RICE PRODUCTION IN NORTHERN MINDANAO, PHILIPPINES - Karen Debbie Jabenar Cosrojas; Sheila C. Poonon; Dante Q. Suminguit (Socio-Economics/Agribusiness Department, 2022)
Organic agriculture is sustainable on the ecological aspect, but other external factors influence its sustainability. The present paper covers the different chokepoints in the sustainability of organic rice production in Northern Mindanao. A total of 380 farmers served as respondents from the five provinces of Northern Mindanao that were selected through purposive sampling. The data were gathered through FGD and personal interviews using a structured questionnaire and data was analyzed descriptively. The study identified production, technical and marketing issues in sustaining the organic rice production. The issues include changing priorities of the Department of Agriculture, unavailability of commercial organic inputs, neighbor rice farm practiced conventional rice production, no price premium received, limited market outlets for organic produce, and high cost of organic certification. The identified issues are areas to be considered for improvement in order to effect improvement and sustainability of organic rice industry in the region.